2020
DOI: 10.1111/1759-7714.13328
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/Akt/mTOR pathway in non‐small cell lung cancer (NSCLC)

Abstract: The traditional classification of lung cancer into small cell lung cancer and non‐small cell lung cancer (NSCLC) has been transformed with the increased understanding of the molecular alterations and genomic biomarkers that drive the development of lung cancer. Increased activation of the phosphatidylinositol 3‐kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) pathway leads to numerous hallmarks of cancer and this pathway represents an attractive target for novel anticancer therapies. In NSCLC, the PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
256
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(278 citation statements)
references
References 85 publications
3
256
0
Order By: Relevance
“…A great deal of evidence had revealed that the AKT signal was heavily implicated in the tumorigenesis, progression, and therapy of cancers including NSCLC. 5,24 Thus, expression of p-AKT was measured, and Western blotting manifested that relative p-AKT expression was suppressed by si-circPRKCA#3 transfection in A549 and H1299 cells ( Figure 2H). These outcomes indicated a suppressive role of circPRKCA knockdown in NSCLC cell growth, migration, invasion, and AKT activity in vitro.…”
Section: Knockdown Of Circprkca Suppressed Cell Growth Migration Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of evidence had revealed that the AKT signal was heavily implicated in the tumorigenesis, progression, and therapy of cancers including NSCLC. 5,24 Thus, expression of p-AKT was measured, and Western blotting manifested that relative p-AKT expression was suppressed by si-circPRKCA#3 transfection in A549 and H1299 cells ( Figure 2H). These outcomes indicated a suppressive role of circPRKCA knockdown in NSCLC cell growth, migration, invasion, and AKT activity in vitro.…”
Section: Knockdown Of Circprkca Suppressed Cell Growth Migration Inmentioning
confidence: 99%
“…4 Furthermore, phosphoinositide 3-kinase (PI3K)/AKT signaling, a key prosurvival pathway in cancer cells, has been proposed as an attractive target for novel anticancer therapies in NSCLC. [5][6][7] Therefore, identifying novel biomarkers that target the PI3K/AKT pathway is of great importance to better understand the malignant development of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins in this pathway are often reported to be mutated or ampli ed in lung adenocarcinomas. Also, the mTOR complex is known to activate AKT through phosphorylation at Serine 473 [34,35]. Our IP data suggests a direct interaction of UBR5 with proteins of the mTOR complex, including Raptor and Rictor.…”
Section: Discussionmentioning
confidence: 64%
“… 37 39 In this study, activation of AKT by phosphorylation was further confirmed when HSP70 was increased, which may further activate mTOR via TSC2 phosphorylation that subsequently stimulates Rheb, which then activates the multiprotein complex mTORC1 and mTORC2. 40 In addition, mTOR inhibitors instead of HSP70 inhibitors were chosen to interfere with this signaling, as mTOR inhibitors could not only suppress the HSP70 induced signaling, but also several other pro-oncogenic pathways. This way, we may allow the use of minimum drug concentrations, but achieve a maximum effect.…”
Section: Discussionmentioning
confidence: 99%